On domains with regular sections - Zelinskii, Yu. B. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We prove the generalized convexity of domains satisfying the condition of acyclicity of their sections by a certain continuously parametrized family of two-dimensional planes.